Ungulate/vegetation dynamics in the Pryor Mountain Wild Horse Range - Peterson, Jan, author; Detling, James K., advisor; Wunder, Bruce A., committee member; Swift, Dave, committee member; Baker, Dan L., committee member (Colorado State University. Libraries, 1999)
I investigated the effects of feral horses, bighorn sheep, and mule deer on structural and functional aspects of vegetation in the Pryor Mountain Wild Horse Range (PMWHR) in southern Montana and northern Wyoming, during 1992 to 1995. I monitored: 1) the biomass dynamics of graminoids, forbs and dwarf shrubs, forage utilization, and the nitrogen content of cool season grasses inside and outside grazing exclosures. 2) vegetation characteristics at the Sorenson Extension site, which had been grazed by feral horses for 10 years before their removal in fall, 1992, and 3) the nutritional dynamics of curlleaf mountain mahogany, an important food resource for wild ungulates. I also estimated protein, fiber, and dry matter digestibility in captive bighorn sheep fed diets containing 40% and 0% curlleaf mountain mahogany. In the arid lowland communities, both live and dead graminoid biomass were greater inside exclosures than outside at two sites in the Dryhead Herd area. After 10 years of horse grazing at the lowland Sorenson Extension site, graminoid biomass was slightly greater outside than inside a fenced area, where horses bad not previously grazed. In the more productive montane sites, live graminoid biomass was two to three times greater inside than outside an exclosure on U.S. Forest Service land Live and dead graminoid biomass were also significantly greater inside than outside the Syke's Ridge exclosure. However, there were no significant differences between graminoid biomass inside and outside the exclosure at the Penn's Cabin site in the upper elevations. Forage utilization ranged from undetectable levels to as high as 43% of the total forb and dwarf shrub production. Although there were no consistent effects of herbivory on plant nitrogen (N) content, live graminoids from upper elevation sites had consistently higher N-concentrations than those from the lower elevations. Because both the quantity and quality of forage were always higher at the upper elevations, these areas appear to be capable of sustaining a larger number of ungulates during the fall and winter seasons. Shrub density, which ranged from 1070 to 54,300 individuals/ha, and seedling density, which ranged from 400 to 49,000 seedlings/ha, were much higher than reported elsewhere. The site with the greatest current annual growth (CAG) production had the highest level of utilization by browsing ungulates, and browsing apparently had no effect on twig biomass or protein concentration. These results suggest that C. ledifolius is capable of compensating for tissue loss. Results from the digestion trial indicate that C. ledifolius depresses protein digestability in bighorn sheep, but reductions in fiber and dry matter digestibility were not statistically significant.
Keywords: ecology; zoology; forestry